POST COVID-19 NEUROLOGICAL SYNDROME (PCNS) IN AN 11 YEARS OLD BOY,A CASE REPORT - Learta Alili Ademi; Filip Duma; Aspazija Sofijanova; Sonja Bojadjieva; Blerim Ademi; Lejla Muaremoska Kanzoska; Danilo Nonkulovski; Katerina Abrasheva; Vesna Jovicic Fidanovska (My University, 2021)
By now more than 92.6[1] persons have been reported to be infected with COVID-19, of which significant part are children. Although children experience milder symptoms compared with adults at the time of the infection, cases of post-covid-19 complications have been reported (2, 3, 4, and 5). Complications might also include the CNS, in our case with cerebellar ataxia-like and polyneuritislike signs and symptoms. A 13 year old boy was presented in our clinic with signs of ataxia, occasional vomiting, impaired gait, impaired patellar reflexes on the right leg, incomplete Babinski reflex on the right leg, paresis of the left facial nerve and mild hypertension. Based on the clinical appearance and the parameters that showed past COVID-19 infection, a diagnosis of Post-COVID19 Cerebellar Ataxia-like and Polyneuritis-like was made, meaning a Post Covid-19 Neurological Syndrome (PCNS). Treatment was conducted with antibiotics and immunoglobulins resulting in significant improvement in the following days. There are few reported cases about neurological complications caused by COVID-19 in children and adolescents, without any other symptoms of the virus. This is one of the first cases of Post- COVID19 Cerebellar Ataxia and Polyneuritis in a child as a result of COVID-19 and the first case in our country.
Keywords: Post-COVID19 complications; Post Covid-19 Neurological Syndrome; cerebellar ataxia; polyneuropathy; children